A Sociolinguistics Analysis: The Comparison of Language Style Used by Beauty Vloggers Sunny Dahye and Amanda Static on Youtube Short (English Language and Literature (JELL), 2026)
This study aims to analyze and compare the language styles used by two beauty vloggers, Sunny Dahye and Amanda Static, in their YouTube Short beauty vlog videos. In addition, this study also aims to explain how social context influences the choice of language styles used by the two beauty vloggers. This study uses a descriptive qualitative approach with data used from 11 YouTube Shorts videos of each vlogger published in the period 2024–2025. This study uses Joos's theory (1967) and the theory of social context and language functions from Holmes (2013). The results of this study found that there are four types of language used by Sunny Dahye, formal, consultative, casual, and intimate, with the casual language style being the most dominant. Meanwhile, Amanda Static only uses three language styles, namely casual, consultative, and intimate, with the dominance of the casual and consultative language styles. These differences in dominant language styles are influenced by each vlogger's social context, including their relationship with their audience, digital communication settings, the topics discussed, and the language functions used. In terms of language functions, Sunny Dahye predominantly uses expressive functions, while Amanda Static predominantly uses referential and directive functions
Keywords: Language style; Language function; Social Context; Beauty Vloggers; Youtube